Implementasi metode sosiodrama untuk meningkatkan keterampilan sosial dalam pembelajaran IPS pada peserta didik kelas V sekolah dasar - Yoshevina Noor Aulya; Siti Istiyati; Yulianti Yulianti (Universitas Sebelas Maret, 2020)
This Classroom Action Research (CAR) was aimed to increased the social skills of students in Social Sciences lessons through used sociodrama method for 5th grade of primary school student at Surakarta on 2019/2020 academic year. This research has two subjects, they were a class teacher and 30 students from 5th grade of primary school. This CAR has procedure research which consisted of two cycles, there was four stages in the each of cycles, that was called planning, action, observation, and reflection. Data collection of this CAR was done by interviewing, observing of social skills, and document studies technique. Data validity in this CAR was used two triangulations, there were triangulation technique and source triangulation. The data analysis was interactive analysis (Miles and Huberman models). The results of the research after the action was increased from initial condition was 44.5 (6.67%) to 60 (46.67%) in the first cycle, and 81 (96.67%) in the second cycle. Based on the results of this CAR, it was concluded that implemented the sociodrama method could increase the social skills in social science lesson of 5th grade primary school students.